Design, Gestaltung, Formatività (De Gruyter, 2024)
What do the work processes of a neurosurgeon and a painter have in common? Applying the notions of “Design”, “Gestaltung”, and “Formatività”, this book sheds new light on processes of formation and transformation in the material world we live in.Scholars from the fields of history, philosophy, psychology, media, and cultural studies question established processes of giving form, while artists, designers, engineers, and scientists describe their creative processes. This book provides its readers with an overview of the spectrum of “philosophies of making” and invites them to reflect on their own creative process, its possibilities, and associated responsibilities to the environment, and ultimately to express these in action. There has never been a more urgent need to develop a new relationship between matter and form. • Discussing and expanding the definitions of “Design”, “Gestaltung”, and “Formatività”• Leading international theorists write about the relationship between matter and form• A collection of new texts and first English translation of key texts.